Tax Study and Financial Performance in the Tourism Industry Post-Pandemic - Rumasukun, Mohammad Ridwan; Noch, Muhammad Yamin (Golden Ratio of Taxation Studies, 2024)
This study conducts a comprehensive literature review to investigate the intersection of taxation policies and financial performance in the tourism industry, particularly in the post-pandemic context. The research aims to examine the impact of the COVID-19 pandemic on tourism financial performance, assess the role of taxation policies in supporting tourism recovery, and identify implications for theory and practice. A systematic review methodology is employed, involving the identification, evaluation, and synthesis of relevant literature from academic databases and scholarly sources. The analysis reveals significant adverse impacts of the pandemic on tourism revenues, profitability, and employment, exacerbating existing vulnerabilities within the sector. Taxation policies emerge as critical instruments for mitigating economic downturns, fostering resilience, and promoting sustainable development in tourism-dependent communities. Key findings underscore the need for flexible and adaptive taxation policies that align with evolving industry dynamics and prioritize social equity, environmental sustainability, and destination competitiveness. Implications for policymakers, industry stakeholders, and destination managers are discussed, emphasizing the importance of collaborative governance, innovation, and stakeholder engagement in shaping a more resilient and inclusive tourism future. The study contributes to theoretical understanding and practical decision-making in the field, offering insights into the multifaceted relationship between taxation policies, financial performance, and destination development in the post-pandemic era.